PENGARUH PEMBERIAN EKSTRAK TEH DAN JUMLAH BIBIT PER LUBANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELEDRI (Apium graveolens L.): PEMBERIAN EKSTRAK TEH DAN JUMLAH BIBIT PER LUBANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELEDRI (Apium graveolens L.) - Rizky Handayani; Priyono Priyono; Saiful Bahri (Innofarm:Jurnal Inovasi Pertanian, 2022)
This study aims to determine the interaction effect of tea extract and the number of seeds per hole on the growth and yield of celery plants. This study used a factorial Completely Randomized Block Design (RAKL), which consisted of 2 factors, each treatment combination replicated 3 times. The two factors were: (1) the number of seeds per hole (S), with 3 levels, namely: S1: 1 seed per hole, S2: 2 seeds per hole, S3: 3 seeds per hole. (2) tea extract, with 4 levels, namely: T0: control, T1: dose of tea extract 1 ml/hole, T2: dose of tea extract 2 ml/hole, T3: dose of tea extract 3 ml/hole, obtained 12 treatment combinations. Analysis of the data using Analysis of Variation (ANOVA), if it is significantly different then a further test is carried out, namely the 5% level BNT test. The results showed that: (1) the interaction between the application of tea extract and the number of seeds per hole did not affect the growth and yield of celery plants, (2) the treatment of tea extract 3 ml/hole with 2 seeds per hole gave the best results on the wet weight of the stover. of 130.77 grams per hole is equivalent to 10.9 tons/Ha. Keywords: Celery, tea extract, number of seeds per hole, growth, yield